Emotional intelligence, motivation and learning strategies: The SSREI and MSLQ-SF questionnaires - Isabel Coronado-Maldonado; Rocío Díaz-Muñoz; José Luis González-Sodis (Intangible Capital)
Purpose: The influence of a good management of Emotional Intelligence (EI) on personal attitude shows a motivational impact that allows better results in any field, work, social or personal. This study analyzes EI and Motivation (MO) through the learning strategies present in 402 university students of the Faculty of Economics and Business and the Faculty of Commerce and Management (Malaga). It also analyzes the impact of gender on these results and identifies the dimensions of the variables studied.